Functional polymers alterations by phylloplane bacteria isolated from crops. (October 2020) - Le Goff, Nicolas; Prost, Elise; Merlier, Franck; Sarde, Claude-Olivier; Falcimaigne-Cordin, Aude; Fayeulle, Antoine
Abstract: The growing uses of functional polymers in different domains and the well-established remanence of synthetic polymers underline the necessity to study their microbial biodegradation. A phylloplane bacterial collection was screened for its potential to overcome documented factors limiting polymer biodegradation, i.e. low cleavable long chain linear polymers and low bioavailable hydrophobic compounds. Acrylate-based polymers, namely poly(2-hydroxyethyl methacrylate) (pHEMA), poly(N-isopropylacrylamide) (pNIPAM), poly(acrylamide) (pAM) and poly(acrylic acid sodium salt) (pAS), and a hydrophobic crosslinker Epoxidized Soybean Oil Acrylate (ESOA) were used as selective substrates. OD monitoring of growth with these molecules as sole carbon sources were correlated with substrates alterations determined by 1 H NMR, GPC and FTIR. Selected strains belong to Bacillales Family XII. Incertae Sedis, Bacillaceae, Nocardiaceae, Micrococcaceae, Enterobacteriaceae and Pseudomonadaceae. Bacillus species mainly developed with ESOA. Exiguobacterium sibiricum strains could grow with pHEMA and pNIPAM leading to polymer molecular weight decreases. Arthrobacter koreensis showed the highest alteration capacities of pHEMA with molecular weight decreases from 22, 000 to 3, 148 g/mol and the production of presumed aromatics and carbon chains. Highlights: 190 bacterial isolates were obtained from the phyllosphere of 4 crops. 17 strains grow with one selective substrates or more (pHEMA, pNIPAM, ESOA). Loss of 83% of ESOA in 4 days with Bacillus sp. 1 and degradation of acrylic groups. Exiguobacterium sibiricum 1 seems to oxidize and cleave pNIPAM backbone. Arthrobacter koreensis hydrolyses lateral groups and main carbon chain of pHEMA.